Demokratia a conversation on democracies, ancient and modern - Ober, Josiah; Hedrick, Charles W. Jr. 1956-. (Princeton, NJ Princeton University Press, 1996)
"This book is the result of a long and fruitful conversation among practitioners of two very different fields: ancient history and political theory. The topic of the conversation is classical Greek democracy and its contemporary relevance. The nineteen contributors remain diverse in their political commitments and in their analytic approaches, but all have engaged deeply with Greek texts, with normative and historical concerns, and with each others' arguments. The issues and tensions examined here are basic to both history and political theory: revolution versus stability, freedom and equality, law and popular sovereignty, cultural ideals and social practice. While the authors are sharply critical of many aspects of Athenian society, culture, and government, they are united by a conviction that classical Athenian democracy has once again become a centrally important subject for political debate
Includes bibliographical references (pages 401-447) and index.
Keywords: Democracy -- Greece -- Athens -- History; Democracy